Instructional Delivery, E-Literacy, and Total Quality Management on Entrepreneurial Competence of Faculty in State Colleges and Universities - Sudaria, Ronel; Paglinawan, James L (International Journal on Integrated Education, 2025)
Abstract: The purpose of this study was to determine the entrepreneurial competence of faculty considering their instructional delivery, e-literacy and total quality management in state colleges and universities in Northern Mindanao, Philippines. The study employed descriptive correlational design with 439 participants. The study revealed that faculty are proficient in instructional delivery in terms of teaching strategy, mastery of the subject matter, classroom management and instructional assessment. Moreover, faculty are literate in e-literacy as measured through technical, pedagogical, ethical and attitudinal. Additionally, the dimensions of total quality management namely: leadership, student-focus, faculty satisfaction and programs/services management was moderately implemented. Furthermore, entrepreneurial competence of faculty in the context of conceptual, human relations, functional and opportunity was competent. The study underscored that instructional delivery, e-literacy and total quality management are significantly related to entrepreneurial competence of faculty. However, instructional delivery—including teaching strategies, instructional assessment, and classroom management—along with total quality management in leadership, program and service management, and e-literacy in technical aspects, were the best predictors of faculty entrepreneurial competence.